An Empirical Study of the Grammatical Competence of Professional Students and the Impact of AI-Assisted and Interactive Mobile Technologies in Enriching Language Competency (International Journal of Food and Nutritional Sciences, 2023)
This study explores the grammatical competence of third-year B.Tech mechanical engineering students and evaluates the role of AI-assisted and interactive mobile technologies in enhancing their language skills. Despite their English-medium education, many students display significant gaps in grammar, which affects their performance in competitive exams and campus recruitment processes. Two grammar tests—pre- and post-intervention—were conducted with a group of 64 students to measure their progress. Between the tests, AI tools and mobile learning platforms such as ChatGPT, Duolingo, and Memrise were introduced to enhance engagement and improve language competency. The results reveal a notable improvement in student performance among those who actively used the technologies, with the highest-scoring group increasing from 8 to 10 students. However, participation declined in the second test, highlighting the need for continuous motivation and engagement strategies. Survey data and observations indicate that gamified learning and real-time feedback provided by the mobile apps fostered higher engagement and boosted students' confidence. Despite these improvements, challenges in sustaining participation persist, indicating that integrating AI tools into regular coursework could be crucial for long-term success.This study demonstrates the potential of AI-powered tools and mobile technologies to bridge grammar learning gaps and prepare students for academic and professional challenges. It recommends incorporating interactive tools into classroom teaching, offering incentives for active participation, and tracking progress through data analytics to provide personalized feedback. These strategies are essential to equip students with the communication skills necessary for career growth and global competence.